Analisis Perhitungan Biaya Standar Guna Meningkatkan Efisiensi Biaya Produksi Pada Konveksi Legging - Pane , Daniella Firstalina; Marliana, Rina; Sirait, Rowendy Tua; Balqisz Maritza, Siti; Lestari, Tri (CV Warnak Johanna Nusantara, 2025)
This study was conducted to analyze the use of standard costs as a means to increase efficiency in production costs in the legging convection business. The background of this study is the inefficiency of its costs caused by waste of raw materials, use of working hours that exceed the limit, and an increase in factory overhead costs. The method approach chosen is qualitative research with a case study technique. Primary data was obtained through direct interviews with the owner of the convection business, while secondary data was collected through observation and documentation of the production process. The findings of the study indicate that there is a significant difference between standard costs and actual costs, which is IDR 11,000 for each product unit. The standard cost for each legging unit is recorded at IDR 50,000, while the actual cost reaches IDR 61,000. This inefficiency, if multiplied by the number of products produced each day of 100 units, will result in a waste of IDR 1,100,000 in a day or around IDR 27,500,000 in a month. These results indicate that the application of a standard cost system can provide a clear picture of the production cost structure, identify sources of waste, and play a role in increasing operational efficiency. Therefore, standard costs can be used as an effective cost control tool in convection production management